2021
DOI: 10.3389/fendo.2021.643328
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Abdominal Lymph Node Metastases of Parathyroid Carcinoma: Diagnostic Workup, Molecular Diagnosis, and Clinical Management

Abstract: Parathyroid carcinoma (PC) is an orphan malignancy accounting for only ~1% of all cases with primary hyperparathyroidism. The localization of recurrent PC is of critical importance and can be exceedingly difficult to diagnose and sometimes futile when common sites of recurrence in the neck and chest cannot be confirmed. Here, we present the diagnostic workup, molecular analysis and multimodal therapy of a 46-year old woman with the extraordinary manifestation of abdominal lymph node metastases 12 years after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…PET/CT is commonly used to detect recurrence or metastasis of malignancies, but its role in PC has not been clearly reported, and only a few case series studies show the benefit of PET scans, especially in the postoperative period, to detect local recurrence and distant metastases, such as subcutaneous recurrence and breast metastasis ( 27 29 ). Only one patient’s liver lesion was found by [18F]FDG-PET-CT among all the cases ( 8 ); such results challenge the sensitivity of [18F]FDG in the diagnosis of liver metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PET/CT is commonly used to detect recurrence or metastasis of malignancies, but its role in PC has not been clearly reported, and only a few case series studies show the benefit of PET scans, especially in the postoperative period, to detect local recurrence and distant metastases, such as subcutaneous recurrence and breast metastasis ( 27 29 ). Only one patient’s liver lesion was found by [18F]FDG-PET-CT among all the cases ( 8 ); such results challenge the sensitivity of [18F]FDG in the diagnosis of liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological saline, diuretics, calcitonin, and bisphosphonates are the most commonly used drugs, which have been clinically demonstrated to lower serum calcium but often only temporarily. The calcimimetic drug cinacalcet is another option that combines with calcium-sensing receptors to reduce PTH secretion and control serum calcium ( 29 ). It can be considered for hypercalcemic patients with inoperable PC, incomplete resection of PC lesions, or postoperative recurrence and effectively lowers serum calcium levels in approximately two-thirds of patients ( 36 , 37 ), but unfortunately, our liver metastatic patients have not shown satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Im Rezidivfall kommen bei häufig erschwerter Lokalisierung die Schnittbildgebungen (Computertomographie, CT/ Magnetresonanztomographie, MRT) sowie Ganzkörperaufnahmen (Positronenemissionstomographie-CT, PET-CT) hinzu [13,18]. In Einzelfällen bedarf es eines selektiven Halsvenenkatheters mit Etagenblutentnahme, um den Rezidivtumor zweifelsfrei zu detektieren [19].…”
Section: Hyperkalzämie Mit Gehäuften Hyperkalzämen Krisenunclassified
“…Neueste Fallberichte zeigen v. a. bei disseminiertem oder metastasiertem Krankheitsverlauf eine Behandlungsoption mit einer gegen humanes Parathormon (hPTH) gerichteten Immuntherapie (Anti-hPTH-Immuntherapie) oder den Einsatz von Immuncheckinhibitoren auf [13,45,46]. Als im komplexen Einzelfall sinnvolle Option konnte der Nutzen einer genomischen Profilerstellung gezeigt werden [19,47,48].…”
Section: Ergänzende Therapieoptionenunclassified
“…In the issue of March 2021, Lenschow et al reported the case of a 46-year-old woman with recurrent, programmed death-ligand-1 (PD-L1) negative, tumor mutational burden (TMB)-high parathyroid carcinoma (PC), who showed stable disease as her best response on imaging, and a three-fold drop in PTH after treatment with intravenous pembrolizumab (1).…”
Section: Introductionmentioning
confidence: 99%